Acute Tramadol-Induced Cellular Tolerance and Dependence of Ventral Tegmental Area Dopaminergic Neurons: An In Vivo Electrophysiological Study - Shabnam Khodayari; Firouz Ghaderi Pakdel; Parviz Shahabi; Somayyeh Naderi (Basic and Clinical Neuroscience, 2019)
Introduction: Ventral Tegmental Area (VTA) is a core region of the brainstem that contributes to different vital bio-responses such as pain and addiction. The Dopaminergic (DA) cellular content of VTA has major roles in different functions. This study aims to evaluate the cellular effect of tramadol on the putative VTA-DA neurons. Methods: Wistar rats were assigned into three groups of control, sham, and tramadol-treated. The animals were anesthetized and their VTA-DA neuronal activity was obtained under controlled stereotaxic operation. The firing rate of the neurons was extracted according to principal component analysis by Igor Pro software and analyzed statistically considering P<0.05 as significant. Tramadol (20 mg/kg) was infused intraperitoneally. Results: Overall, 121 putative VTA-DA neurons were isolated from all groups. In tramadol-treated rats, the inhibition of the neuronal firing was proposed as tolerance and the excitation period as dependence or withdrawal. The Mean±SD inhibition time lasted up to 50.34±10.17 minutes and 31% of neurons stopped firing and silenced after 24±3 min on average but the remaining neurons lowered their firing up to 43% to 67% of their baseline firing. All neurons showed the excitation period, lasted about 56.12±15.30 min, and the firing of neurons increased from 176% to 244% of their baseline or pre-injection period. Conclusion: The tolerance and dependence effects of tramadol are related to the changes in the neuronal firing rate at the putative VTA-DA neurons. The acute injection of tramadol can initiate neuroadaptation on the opioid and non-opioid neurotransmission to mediate these effects.